Pengaruh Citra Merek dan Kualitas Pelayanan melalui Customer Experience terhadap Loyalitas Pelanggan Gojek di Jabodetabek - Vanisyati, Zefitiazhar Ken Rifda; Nora, Liza (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This research is entitled "The Influence of Brand Image and Service Quality through Customer Experience on Gojek Customer Loyalty in JABODETABEK". The purpose of this study is to determine the influence of Brand Image and Service Quality mediated through Customer Experience on Customer Loyalty in Gojek users in JABODETABEK, with a Case Study of the Phenomenon of Brand Image and Gojek Service Quality which has decreased. This study uses a quantitative research design with an associative method. Data collection was carried out by distributing a questionnaire to all respondents who had used and purchased Gojek services as many as 196 respondents. The sampling technique is using the lemeshow formula. The data processing in this study uses Smart PLS 4. The results of the study show that the Brand Image variable has a positive and significant effect on Customer Experience, Brand Image has a positive and significant effect on Customer Loyalty, Customer Experience has a positive and significant effect on Customer Loyalty, Service Quality has a positive and significant effect on Customer Experience, Service Quality has a positive and significant effect on Customer Loyalty, Brand Image mediated by Customer Experience has a positive and significant effect on Customer Loyalty and Service Quality mediated by Customer Experience has a positive and significant effect on Customer Loyalty.